Poly[(μ(2)-benzene-1,3-dicarboxylato-κ(2) O (1):O (3)){μ(2)-1,2-bis[(1H-imidazol-1-yl)methyl]benzene-κ(2) N (3):N (3′)}zinc] - Chen, Hong (International Union of Crystallography, 2012)
In the two-dimensional title coordination polymer, [Zn(C(8)H(4)O(4))(C(14)H(14)N(4))](n), the Zn(II) atom adopts a distorted tetrahedral geometry, being ligated by two O atoms from two different benzene-1,3-dicarboxylate dianions and two N atoms from two symmetry-related 1,2-bis(imidazol-1-ylmethyl)benzene molecules. The dihedral angles between the imidazole rings and the benzene ring in the neutral ligand are 76.31 (13) and 85.33 (15)°. The Zn(II) atoms are bridged by dicarboxylate ligands, forming chains parallel to the a axis, which are further linked by 1,2-bis(imidazol-1-ylmethyl)benzene molecules, generating a two-dimensional layer structure parallel to the ac plane. The crystal structure is enforced by intralayer and interlayer C—H⋯O hydrogen bonds.